A low-energy and sustainable pulping technology for eucalyptus slabs using a deep eutectic solvent. Issue 8 (4th April 2023) - Zhang, Zhaohui; Xu, Jun; Xie, Junxian; Zhu, Shiyun; Li, Jun; Ying, Guangdong; Chen, Kefu
Abstract : An integrated pulping process was proposed that simultaneously produced pulp and useful lignin by-product from eucalyptus along with the recycling of chemicals and water. Abstract : Carbon reduction targets urge people to develop potential alternatives to traditional energy-intensive kraft pulping. To address this need, this work reported a sustainable pulping technology for eucalyptus slabs based on a deep eutectic solvent (DES) consisting of benzyltriethylammonium chloride (BTEAC) and formic acid (FA). Under mild cooking conditions ( T = 130 °C, t = 2.0 h), the pulp yield reached 53.83%, and fibers had a length of 0.65 mm and a fines content of 6.21%. The physical properties of DES pulp were similar to those made by other traditional processes. Meanwhile, approximately 85% of FA and 92% of BTEAC could be reused in the improved chemical recovery process, and the cooking efficiency of recycled DES was largely maintained after 5 times of recycling. Moreover, compared with the kraft process, DES pulping could extract more lignin with high purity and narrow molecular weight distribution. The results proved that this technology could produce high-quality pulp and lignin by-products simultaneously with less energy and chemical consumption.